Управління оборотними коштами, вкладеними у виробничі запаси - Мельникова, Ю. В. (My University, 2013)
Досліджено суть та необхідність управління оборотними коштами підприємства. Визначено сутність поняття «оборотні кошти», а також завдання управління оборотними коштами підприємства. Investigated the nature and the need to manage working capital. The essence of the concept of "working capital" and the challenge of working capital.
Keywords: оборотні кошти; управління оборотними коштами; нормовані оборотні активи; ненормовані оборотні активи; current assets; management of working capital; normalized current assets; nonnormable current assets